Impact of rice gruel on rumen metabolites and growth performance of sheep - Das, Tridip; Hasanuzzaman, Md.; Rana, Eaftekhar Ahmed; Deb, Probir; Roy, Sri Rajiv Kumar; Bari, Md. Saiful (Journal of Advanced Veterinary and Animal Research, 2018)
Objectives: We investigated the impact of rice gruel as an alternative energy source of molasses as well as measured the effectiveness of rice gruel on the physiology of the rumen environment and the growth performance of growing lamb. Materials and methods: A number of 18 sheep with an average age of 7 months and mean body weight of 5.9 kg were selected and divided into three groups for 60 days long feeding trial with urea molasses straw (UMS), urea rice gruel straw (URS), and concentrate feed. Every fortnight interval, live weight was recorded and rumen liquor from every group was collected four times before and after feeding at 4-h interval to examine the rumen environment. Results: Color, odor, consistency, and protozoal motility remain unchanged in all three groups. The pH of the rumen liquor was highest at 8 h of post feeding among three groups. The bacterial count (6.1 × 1010) was higher in the group that consuming UMS than URS and concentrate feed. The rumen protozoa also showed a similar growth pattern in proportion to a number of rumen bacteria. At the end of the 60 days feeding trial, no significant differences (p ≤ 0.05) were found among the three groups in contrast to body weight gain. Conclusion: In the current feeding trial, the close similar effectiveness of rice gruel and molasses was found as a fermentable energy source. However, we suggest that rice gruel can be supplemented as a substitute for molasses under the situation when molasses are not available or expensive in field condition. http://doi.org/10.5455/javar.2018.e295